MEDICINAL PLANTS USED IN NEERILIVU (DIABETES MELLITUS) IN TRADITIONAL MEDICINE - REVIEW AND ASSESSMENT OF SCIENTIFIC EVIDENCES (International Journal of Ayurveda and Pharma Research, 2021)
Introduction: Sarapenthira  vaithiya murailkal (Neerilivu chikitchai) (SVM-NC) is a classic book written in a poetic form. It mentioned the treatment of Neerilivu (Diabetic Mellitus (DM)). According to the mode of administration, Siddha medicines are categorized into two classes; Internal medicine & external medicine. Medicinal plants, Metals and Minerals are used to prepare medicines from ancient times for the treatment of Neerilivu (DM). According to the Siddha literatures signs & symptoms of Neerilivu can be compared with Diabetic Mellitus in modern aspect. Diabetic Mellitus is a chronic metabolic disorder. Many drugs are mentioned for the treatment of Neerilivu (DM) in SVM-NC. Aim: The aim of the study is to identify the types of Siddha drugs and its ingredients from SVM-NC and research article. Data were collected, tabulated and analysed. This information was used to identify the medicinal plants that are being used in the management of Neerilivu (DM) in the traditional medicine. Results and Discussion: Eighty-five drugs were identified from the analysis. Out of 85 drugs, 83 drugs (98%) are used as internally and 2 drugs (2%) are externally. Among the 85 Internal medicine, 28 (33%) are chooranum, 20 (24%) are home remedy, 12 (14%) are kudineer and 8 (9%) are vizhuthu. Two external medicines are oil. 124 medicinal plants were identified from 83 internal medicines. 63 Families were identified in 124 medicinal plants. 10% (26) Medicinal plants are belonging to Fabaceae family. From these plants, 34 (27%) plants are used as root, 19 (15%) plants are used as leaves and seeds and 17 (14%) plants are used as bark. These plants have siddha properties; taste (Astringent: 41 (33%), Bitter: 32 (26%), Sweet: 28 (23%)), Potency (Hot: 81 (61%), Cool: 37 (30%)) and Efficacy (Pungent: 68 (55%), Sweet: 50(40%)). Among the 85 drugs, Cassia auriculata, Phyllanthus emblica, Strychnos potatorum, Terminalia chebula, Terminalia bellirica, Sysygium aromaticum and Salacia reticulata are used many times in medicine preparation.  Previous researches showed that these ingredients have antidiabetic activity, hepatoprotectives and anti-oxidant. Conclusion: This review provides useful documented evidence and scientific evidence on the treatment of Neerilivu (DM) in traditional medicine.